Design optimisation of Propeller Boss Cap Fins for enhanced propeller performance. (January 2017) - Mizzi, Kurt; Demirel, Yigit Kemal; Banks, Charlotte; Turan, Osman; Kaklis, Panagiotis; Atlar, Mehmet
Highlights: A design optimisation procedure for Energy Saving Devices at full scale is proposed. Validation and verification procedures for the numerical open water test simulations were presented. Propeller Boss Cap Fins geometry were parametrically modelled being able to produce various designs ready for automation. An optimisation system framework using a parametric modeller, a flow solver and a high performance computer was described. The functions and physics behind Propeller Boss Cap Fins were analysed and further investigated. Abstract: Economic pressures and regulatory requirements have brought about a great interest in improving ship propulsion efficiency. This can be exercised by installing Energy Saving Devices (ESD) such as Propeller Boss Cap Fins (PBCF). This paper demonstrates an approach for optimising PBCF by using Computational Fluid Dynamics (CFD) analysis. The conducted Reynolds-averaged Navier-Stokes (RANS) CFD open water model tests were validated by comparison with experimental data until the simulation was deemed satisfactory within the capabilities and limitations of the model. A design and optimisation procedure was defined to analyse the impact of ESDs on propeller efficiency and then used to evaluate the influence of alternative geometric parameters and locations of the PBCF on the hub. This analysis was done at full scale using high fidelity CFD-based RANS methods. Outcomes of the study include a design and optimisation process that can be used for the analysis of other ESDs on the market. The influences of various PBCF geometry were examined with optimal solutions presented for the analysis case. Results indicated a net energy efficiency improvement of 1.3% contributing to a substantial minimisation of cost and energy consumption. A reduction in the hub vortex was also clearly identified and presented.